Kajian Fitokimia dan Aktivitas Pencernaan Buah Nanas (Ananas comosus) dalam Mendukung Nafsu Makan - Annisa Tuzzahra; Ardi Mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Pineapple (Ananas comosus) is a tropical fruit widely consumed and recognized for its potential role in supporting digestive health and appetite enhancement. This potential is associated with its phytochemical composition and digestive enzymes, particularly bromelain, which facilitates protein breakdown and improves digestive efficiency. This study aimed to review the phytochemical profile and digestive activity of pineapple based on scientific literature. A literature review method was applied using relevant national and international publications, focusing on bioactive compounds, analytical methods, and biological activities related to digestion and appetite. The findings indicate that pineapple contains bromelain, flavonoids, phenolic compounds, vitamin C, and dietary fiber. These components contribute to enhanced digestive enzyme activity, improved gastrointestinal function, and indirect appetite stimulation through better digestion. In addition, the antioxidant and anti-inflammatory properties of pineapple support gastrointestinal health. Overall, pineapple shows potential as a functional food to support digestion and appetite